Enfoque de auditoría de gestión para el sector florícolacaso empresa Yanita Flowers Cía. Ltda., por el período del 1 de enero al 31 de diciembre del 2013 - Semblantes Calahorrano, Valeria Katherine (2014)
The present approach of management audit carried out at Yanita Flowers C.O. in the flower market, in the period of January lst to December 31st , 2013, consists of a methodological practice that fusions concepts of ISO 19011, “Guidelines for management audit”, according to what was established by Benjamín Franklin, 2007 in his book “Administrative Audit, Strategic Management for change”. In addition, it counts on a complete analysis of the Porter Five Forces, Pestel Analysis, SWOT analysis, and finally B.C.G analysis. Later, management indicators for the areas examined were designed, which are interpreted based on a traffic light structure, since that with this structure, genuine and integral information is obtained and the real condition of the company is reflected.